Adjustments of local labour markets to the COVID-19 crisis: The role of digitalisation and working-from-home - Sarra Ben Yahmed; Francesco Berlingieri; Eduard Brüll (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Employment responses to the COVID-19 crisis differed widely across German local labour markets at the beginning of the pandemic, with differences in short-time work rates of up to 20 percentage points. We show that digital capital, and to a lesser extent working-from-home, were essential for the resilience of local labour markets. Using an empirical strategy that combines a difference-in-differences approach with propensity score weighting, we find that local exposure to digital capital reduced short-time work usage by up to 4 percentage points and the effect lasted for about 8 months. Working-from-home potential lowered short-time work rates, but only in local labour markets exposed to digital capital, and in the first four months of the pandemic when a strict lockdown was in place. Differences in unemployment rates across local labour markets were at most 2 percentage points and did not depend on digital capital or working-from-home potential.
Keywords: J21; O3; R12; R23; 330; COVID-19 crisis; Digitalisation; Employment; Information and communication technologies; Local labour markets; Short-time work; Working-from-home